Trade Unions, Forced Labour and Human Trafficking - Ford, Michele (Anti-Trafficking Review, 2015)
This article examines the dilemmas facing trade unions seeking to engage on questions of forced labour and human trafficking. The International Labour Organization and elements of the international trade union movement have succeeded in getting forced labour on the policy agenda globally and within many national settings. However, trade unions have limited capacity to effect real change in relation to these issues because of limitations on their influence, determined largely by membership density and the limited number of sectors in which they are present, but also internal assessments of what constitutes ‘core business’. As a consequence, while trade unions may advocate for legislative or policy change, partner with non-governmental organisations to deal with particular cases, or even engage directly with vulnerable populations, the integration of those populations into the day to day concerns of trade unions necessarily remains elusive—particularly in the global south, where forced labour is most prevalent.